Impulsivity and Rapid Decision-Making for Reward - Burnett Heyes, Stephanie; Adam, Robert; Urner, Maren; van der Leer, Leslie; Bahrami, Bahador; Bays, Paul M.; Husain, Masud (Frontiers in Psychology, 2012)
Impulsivity is a feature of many brain disorders. Although often defined as the predisposition to act with an inadequate degree of deliberation, forethought or control, it has proven difficult to measure. This may in part be because, increasingly, impulsivity is recognized as a multifaceted construct, with impulsive decisions potentially arising due to a number of underlying mechanisms. Indeed, in certain contexts, a ‘functional’ degree of impulsivity may promote effective, motivated behavior in healthy participants. Although many tasks have been developed to study impulsivity, few examine decisions made rapidly, for time-sensitive rewards: In this context, a degree of impulsivity may be adaptive. In the current study we examine behavior in 59 adults on a manual ‘Traffic Light’ task which requires participants to take risks under time pressure, if they are to maximize reward. We show that behavioral variables that index rapid anticipatory responding in this paradigm are correlated with a specific self-report measure of impulsivity: ‘lack of premeditation’ on the UPPS Impulsive Behavior Scale. Participants who scored more highly on this subscale performed better on the task. Moreover, anticipatory behavior reduced significantly with age (18-79 years), an effect that continued to be upheld after correction for potential age differences in the ability to judge the timing of responses. Based on these findings, we argue that the Traffic Light task provides a parametric method to study a ‘functional’ aspect of impulsivity in health and disease: namely, rapid decision-making in pursuit of risky, time-sensitive rewards.